Pertolongan Pertama terhadap Lawan Jenis (Non Mahram) pada Kecelakaan Perspektif Kaidah al-Ḍarūrātu TubῙḥu al-Maḥẓurāt: First Aid for the Opposite Sex (Non Mahram) in Accidents from the Perspective of the Principle of Al-Ḍarūrātu TubῙḥu Al-Maḥẓurāt - Asri, Asri; Afrianto, Afrianto; Ahmad Yani (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to determine how the implementation of the principle of al-Ḍarūrātu Tubῑḥu al-Maḥẓurāt in first aid. This study uses a qualitative descriptive type of research, (non-statistical), using the library research method (Literature review), using the normative juridical approach and philosophical approach. The results of the study are as follows: first, First aid is the initial action given to someone who is injured or suddenly ill before professional medical assistance arrives, with the aim of saving lives, preventing bad conditions, and carrying out the recovery stage. The steps that must be taken are ensuring safety, assessing the victim's condition, and carrying out actions such as CPR, stopping bleeding, or providing respiratory assistance. Second, the rule of al-Ḍarūrātu Tubῑḥu al-Maḥẓurāt in Islamic law states that emergency situations permit things that are forbidden to protect life or prevent major danger, provided that the action is according to need and does not exceed the necessary limits, such as touching a non-mahram opposite sex in an emergency is permitted if there is no other alternative. Third, according to this rule, first aid for the opposite sex is permitted in life-threatening emergency situations, if there are no other helpers around the victim except the opposite sex. However, if there is an expert in first aid who is the same sex as the victim, then they are more recommended to provide assistance.